2012
DOI: 10.1308/003588412x13171221589720
|View full text |Cite
|
Sign up to set email alerts
|

Total hip replacement for the treatment of acute femoral neck fractures: results from the National Joint Registry of England and Wales at 3-5 years after surgery

Abstract: INTRODUCTION This paper describes, for the first time, the outcomes of patients undergoing total hip replacement for acute fractured neck of femur (#NOF) as recorded by the National Joint Registry of England and Wales (NJR). METHODS In the NJR we identified 1,302 of 157,232 Hospital Episode Statistics linked patients who had been recorded as having a total hip replacement for acute #NOF between April 2003 and November 2008. RESULTS The revision rate at five years for fully uncemented components was 4.1% (95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 17 publications
3
25
0
Order By: Relevance
“…However, because of this long going tradition the majority of the studies published regarding whether the use of cement or not has been made with HA stems – a debate which is still controversial despite continuous research [ 7 9 ]. For THA stem, very little has been published on the subject [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, because of this long going tradition the majority of the studies published regarding whether the use of cement or not has been made with HA stems – a debate which is still controversial despite continuous research [ 7 9 ]. For THA stem, very little has been published on the subject [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, THA has been shown to have a superior longevity, lower revision rates, and higher functional outcome scores [4][5][6]. Results from the National Joint Registry of England and Wales have shown that the probability of implant survival for patients with femoral neck fractures treated with primary THA is comparable with the implant survival in patients with THA for other indications [7]. The most common cause for patient dissatisfaction after HA is groin pain as a result of acetabular erosion [2,8,9].…”
mentioning
confidence: 99%
“…2012, Stafford et al. 2012). The early mortality after THA is thus considerably lower than after hemiarthroplasty, where an in-hospital mortality of 5.7% has been described (Ginsel et al.…”
mentioning
confidence: 99%